DEVELOPMENT OF INNOVATIVE-EDUCATIONAL NETWORK IN HIGHER EDUCATION SERVICES: https://doi.org/10.5281/zenodo.16812358 - Kodirov , Javohir (Journal of Contemporary World Studies, 2025)
The article provides practical recommendations and suggestions on socio-economic relations arising in the process of development and evaluation system of Higher Education Services, factors affecting the competitiveness of graduates in the labor market and the level of quality of higher education services.